Analisis Beban Kerja untuk Optimalisasi Produktivitas Tenaga Kerja pada Lini Produksi Mesin Pond (Studi kasus: UD. XYZ) - Wibisono, Satria Abdi; Purnama, Jaka (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study analyzes workload and determines the optimal number of workers on the pond machine production line at UD. XYZ  using Workload Analysis (WLA) method and stopwatch time study. Data were collected through direct observation of 7 workers with 24 observations per work station during July-November 2025. The results show significant workload imbalance: the blade board manufacturing station experienced 446% overload, pond processes for Ivory 310, Duplex 350, and Duplex 310 were 185%, 191%, and 192% respectively, while plano paper cutting, QC cleaning, and packaging stations experienced underload below 75%. Standard time for pond processes ranged from 7.79-8.01 minutes. The study recommends adding 3 workers (total 10 people) with optimal redistribution to reduce workload to 46-111%, saving operational costs of Rp 10,368,000 per month (27%) while increasing productivity to achieve the target of 2,000 units per day.